Public Ends, Private Means : Strategic Purchasing of Health Services - Preker, Alexander S.; Liu, Xingzhu; Velenyi, Edit V.; Baris, Enis (Washington, DC: World Bank, 2012)
Public Ends, Private Means: Strategic purchasing of value for money in health services is part of a series of World Bank publications on ways to make public spending on health care more efficient and equitable in developing countries. It reviews the underlying economics in terms of agency theory, behavioral science, contract theory, transaction costs, and public choice theory. It provides a synthesis of the institutional environment needed for countries to shift to strategic purchasing, organizational incentives that need to be in place, and management capacity that needs to be strengthened. The volume is supplemented with a CD that presents six regional reviews of current resource allocation and purchasing (RAP) arrangements.